TIGIT: A Key Inhibitor of the Cancer Immunity Cycle. Issue 1 (January 2017) - Manieri, Nicholas A.; Chiang, Eugene Y.; Grogan, Jane L.
Abstract : Immunotherapies that harness the activity of the immune system against tumors are proving to be an effective therapeutic approach in multiple malignancies. Indeed, through accumulation of genetic mutations, many tumors express antigens that can potentially elicit specific tumor immunity. However, tumors can also suppress these responses by activating negative regulatory pathways and checkpoints such as PD-1/PD-L1 and CTLA-4. Blocking these checkpoints on T cells has provided dramatic clinical benefit, but only a subset of patients exhibit clear and durable responses, suggesting that other mechanisms must be limiting the immune response. We discuss here the role of TIGIT, an inhibitory receptor expressed by lymphocytes, in limiting antitumor responses and we review its mechanisms of action during the cancer immunity cycle. Trends: TIGIT is an inhibitory immunoreceptor expressed on lymphocytes and has been studied in the context of autoimmunity, viral immunity, and cancer. TIGIT is an important inhibitory molecule within the PVR/nectin family, and is associated with human cancers and T cell exhaustion phenotypes. Inhibition of TIGIT can enhance antitumor T cell responses through its role as a ligand, receptor, and competitor for the costimulatory receptor CD226. TIGIT is expressed on several important immune cell types and may have different functions on different cell types. TIGIT is an attractive cancer immunotherapy target owing to its role in many of the steps that generate cancer immunity.